Terapi Sel Punca sebagai Inovasi dalam Pengobatan Penyakit Autoimun untuk Mempertahankan Sistem Imunitas Tubuh Manusia - Elysabeth Simatupang; Pahotkon Purba; Sherina Juliana; Yohana Ayustin; Wahyu Irawati (Jurusan Biologi FMIPA Universitas Cenderawasih, 2022)
Autoimmune is a disease caused by imbalance of immunology and losing tolerance then causes autoimmunity to attack body tissues in organisms. This disease occurs when the self-antigens attached by adaptive immune response. This disease can be treated by stem cell therapy. Stem cell therapy is an assured alternative to autoimmune treatment. Stem cells that can differentiate or can change themselves into various cells according to the environment and function to replace the damaged body cells. This study aims to find out the utility of stem cell therapy as an innovation in the treatment of autoimmune diseases. Literasture review is the method used in this research and focus to discuss: 1) the body's immune system; 2) immune system disorders; 3) autoimmune disease mechanisms; and 4) Stem cell therapy as an alternative to autoimmune treatment. Through this paper, readers will know that there is one technology to use treating autoimmune diseases, stem cell therapy. The mechanism of utilisation of stem cell therapy varies with each type of autoimmune disease, but this therapy can also cause some side effects. Stem cell therapy repairs damaged cells and replaces them with new, more functional ones. Key words: autoimmune disease; stem cell therapy; human body; medication.